2009
DOI: 10.3174/ajnr.a1637
|View full text |Cite
|
Sign up to set email alerts
|

[18F] Fluorodeoxyglucose–Positron-Emission Tomography and MR Imaging Coregistration for Presurgical Evaluation of Medically Refractory Epilepsy

Abstract: SUMMARY:Epilepsy is a chronic disorder affecting approximately 1% of the population of the world. Approximately one third of patients with epilepsy remain refractory to medical therapy. For these patients, surgery is a curative option. In order for surgery to be considered, precise localization of the structural abnormality is needed. When MR imaging findings are normal, more sensitive techniques such as positron-emission tomography (PET) can help find the abnormality. Combining MR imaging and PET information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 44 publications
0
30
1
1
Order By: Relevance
“…In these cases, further evaluation with nuclear medicine techniques including [ 18 F]-FDG PET and ictal/interictal perfusion SPECT is indicated [30]. In these cases, coregistration of the PET/SPECT and MRI data leads to improved detection of epileptogenic foci [31]. Importantly, patients without MRI lesions, and with positive PET scans, have similar outcomes to those with MRI findings following epilepsy surgery [32,33].…”
Section: Epilepsymentioning
confidence: 93%
“…In these cases, further evaluation with nuclear medicine techniques including [ 18 F]-FDG PET and ictal/interictal perfusion SPECT is indicated [30]. In these cases, coregistration of the PET/SPECT and MRI data leads to improved detection of epileptogenic foci [31]. Importantly, patients without MRI lesions, and with positive PET scans, have similar outcomes to those with MRI findings following epilepsy surgery [32,33].…”
Section: Epilepsymentioning
confidence: 93%
“…Studies combining MRI and [ 18 F]FDG PET in the presurgical assessment of refractory epilepsy (i.e. medial temporal sclerosis, focal cortical dysplasia and tuberous sclerosis complex) are numerous and have recently been reviewed by Lee and Salamon [91]. Briefly, they found that coregistration of [ 18 [94].…”
Section: Pet/mri In Epilepsymentioning
confidence: 98%
“…Aberrant brain function then needs to be assessed using other noninvasive imaging modalities such as magnetoencephalography, SPECT and PET. Interictal [ 18 F]FDG PET, that shows hypometabolism in epileptogenic foci, was the first imaging modality used in the planning of surgery for TLE [90] and is now routinely used in specialized PET centres [91]. Studies combining MRI and [ 18 F]FDG PET in the presurgical assessment of refractory epilepsy (i.e.…”
Section: Pet/mri In Epilepsymentioning
confidence: 99%
“…Using our knowledge of normal physiology, this comparison has been used to describe how the complexity of EEG recording during seizure (ictus) is less than that of interictal EEG [1, 2]; how epileptic lesions are associated with focal cortical atrophy and hyperintensity on MRI [12]; and how focal interictal hypometabolism in FDG-PET can indicate the seizure onset zone [13]. These differences are thought to be macro-scale features that confirm our understanding of epilepsy on a neural level.…”
Section: Introductionmentioning
confidence: 99%